Role of Hepatitis B virus X protein (HBx) in cell adhesion and cytoskeletal reorganization : implications on virus replication - Tan, Tuan Lin (2008)
HBV genotypes have been linked to differential liver disease outcomes. For genotypes that are predominant in Asia, HBV genotype B has been shown to lead to hepatocellular carcinoma while the genotype C has been associated with more invasive liver disease. Using 2-Dimensional Electrophoresis, we identified differences in proteome expression profiles in cells transfected with constructs expressing distinct genotypes of the smallest HBV protein, HBx, which has been linked to oncogenic development. Through the use of bacterial-expressed proline-rich region from HBx, we identified multiple interacting partners containing SH3 domains on a protein array. Many of these serve important roles in cell cytoskeleton maintenance and cellular signaling. In particular, we showed that Vinexin ? (a binding partner of vinculin for the formation of focal adhesion complex) interacted with HBx through the PXXP motif. This provided molecular understanding on the delay in cell adhesion associated with either the HBV replication or HBx expression, as we observed concurrently. Significantly the delay in adhesion was restored in cells transfected with HBx construct containing proline to alanine mutations within the PXXP motif. Our results suggested that HBx was directly involved, via the SH3 binding domain, in the cytoskeletal reorganization leading to alterations in the cell adhesion process. To determine the functional significance on HBV replication, structural analysis by Atomic Force Microscopy and fluorescent microscopy was carried out in cells supporting HBV replication and those expressing Rho p21 proteins which are key players in cellular cytoskeletal reorganization. We showed that cells expressing the constitutively activated Rac1 displayed similar morphology to those supporting HBV replication. Moreover, we showed that HBV activated Rac1 specifically compared to Cdc42 through activated-GTPase binding assay to PAK1 Cdc42/Rac1 interactive binding (CRIB) domain. Significantly, we showed that both activated Rac1 and Cdc42 led to an up-regulation of HBV viral replication as evidenced by increased viral intermediates through quantitative Real Time-RT-PCR. Transient transfections of HBx have been shown to result in similar phenotypic morphology as rHBV transfected cells and it was also shown to be potentially interacting with ?PIX, a RhoGEF responsible for Rac1 activation.